Late-season source limitation practices to cope with climate change: delaying ripening and improving colour of Cabernet-Sauvignon grapes and wine in a hot and arid climate - Luca Pallotti; Guadalupe Partida; Eve Laroche-Pinel; Vania Lanari; Miguel Pedroza; Luca Brillante (OENO One)
The current rise in temperatures is hastening grape ripening, resulting in unbalanced wines with high alcohol content but poor colour, aroma and phenolic composition. Late-season canopy manipulation practices aimed at reducing the size of the photosynthetic apparatus after veraison have been shown to delay ripening in cooler climates. However, these methods have not directly been compared in regions with high irradiance and temperature, where berry composition is negatively affected by late fruit exposure.